2016
DOI: 10.1177/1759313116649967
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of using a spectral hindcast database for wave power extraction assessment

Abstract: When considering deployment of wave energy converters at a given site, it is of prime importance from both a technical and an economical point of view to accurately assess the total yearly energy that can be extracted by the given device. Especially, to be considered is the assessment of the efficiency of the device over the widest span of the sea-states spectral bandwidth. Hence, the aim of this study is to assess the biases and errors introduced on extracted power classically computed using spectral data der… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…An analysis based on the JONSWAP spectrum exhibited a slight overestimation when compared to hindcast data and yielded large instant errors due to its focus on unimodal sea states. This focus prevented the model from accurately assessing the spectral distribution of the native energy found in this region [26]. When Campos and Soares [27], compared 3 hindcast models: the ERA-Interim, NOAA (based on WAVEWATCH III) and HIPOCAS (based on the REMO wind model), they found that at non-extreme conditions the hindcasts were effectively equivalent as their biases for significant wave height was less than 0.5 m. However, when comparing wind and wave errors, WAVEWATCH III was the best model for accuracy and was suggested to be the model of choice for latitudes below 30 • North (as is the case in this study).…”
Section: Discussionmentioning
confidence: 99%
“…An analysis based on the JONSWAP spectrum exhibited a slight overestimation when compared to hindcast data and yielded large instant errors due to its focus on unimodal sea states. This focus prevented the model from accurately assessing the spectral distribution of the native energy found in this region [26]. When Campos and Soares [27], compared 3 hindcast models: the ERA-Interim, NOAA (based on WAVEWATCH III) and HIPOCAS (based on the REMO wind model), they found that at non-extreme conditions the hindcasts were effectively equivalent as their biases for significant wave height was less than 0.5 m. However, when comparing wind and wave errors, WAVEWATCH III was the best model for accuracy and was suggested to be the model of choice for latitudes below 30 • North (as is the case in this study).…”
Section: Discussionmentioning
confidence: 99%
“…Many documents (e.g. [9] and [10]) highlight errors which can be made when power capture is estimated using seastate spectrum which does not represent the actual measured spectrum. This prompts questions about how representative scale site spectra are of a commercial site, and whether scale sites with more representative spectra can be found?…”
Section: A Interesting Questions Arisingmentioning
confidence: 99%
“…Utilization of this information by the marine industry is strongly recommended. For instance, when investigating the response of an offshore structure, spectral hindcast databases, composed of time series of wave spectra, whenever available, should be used preferably to sets of spectra built from analytical formulations such as JONSWAP(Hasselman et al, 1973), because of the inability of such theoretical unimodal forms, characterized by a single set of three global parameters, to correctly account for the spectral distribution of the wave energy in the case of complex sea-states(Maisondieu and Le Boulluec, 2015).…”
mentioning
confidence: 99%